Treat-to-target versus dose-adapted statin treatment of cholesterol to reduce cardiovascular risk. (29th August 2020) - Müller-Wieland, Dirk; Assmann, Gerd; Carmena, Rafael; Davignon, Jean; von Eckardstein, Arnold; Farinaro, Eduardo; Greten, Heiner; Olsson, Anders G; Riesen, Walter F; Shlyakhto, Evgenyi
Abstract: Clinical guidelines should be based on the best available evidence and are of great importance for patient care and disease prevention. In this respect, the 2013 American College of Cardiology/American Heart Association report is highly appreciated and well-recognized. The report included critical questions concerning hypercholesterolaemia, but its translation into a clinical guideline initiated intense debate worldwide because of the recommendation to switch from a treat-to-target approach for low-density-lipoprotein-cholesterol to a statin dose-based strategy.